PERCEPTION OF STIGMA: PARENTS OF CHILDREN WITH SEN IN MAINSTREANSCHOOLS IN NUR-SULTAN - Aitbayeva, Anzhela (Nazarbayev University Graduate School of Education, 2022)
The Republic of Kazakhstan has established a comprehensive legal framework by regulating its provisions for including children with disabilities in mainstream education. According to this framework, appropriate conditions are to be designed in pre-school and secondary educational organizations that bridge joint education for children with special needs and typically developing children. Despite efforts made to spread sufficient national legal and regulatory framework by the state, the stigmatization of children with disabilities and their family members has ambivalent attitudes in terms of equal recognition of their diversity, rights, and participation, on the one hand, and the fact that they are not fully recognized by society as active members, on the other. The stigmatization, social prejudices, stereotypes and discrimination of children with disabilities and their family members appear to prevail in Kazakhstani education. Yet, the research on stigma in education is still scanty and extremely limited in Kazakhstan. This study attempts to bridge the gap in the literature by exploring stigmatization attitudes and practices which can seriously impede the successful development of contemporary inclusive education in the national context. A qualitative method was employed as a research design for this study. Semi-structured interviews were conducted to explore the perception of the stigma of five parents whose children with disabilities were enrolled in the mainstream schools in Nur-Sultan. The present study highlighted the main findings on the perception of stigma from parents’ points of view that are considered complex and ambiguous. The overall research findings showed that parents whose children with disabilities studied in mainstream schools in Nur-Sultan experienced stigma. However, slight differences were identified in the parents’ responses on how they experienced stigma. The findings also highlighted parents’ expectations from school in terms of enhancing awareness of the school community about the profile of children with disabilities and their educational needs, building collaboration in the school-parents-children network, and promoting a positive model of attitudes toward children with disabilities and their families. The outcomes of this study suggest that stigmatization and discrimination of children with disabilities and their families require developing and incorporating effective strategies of antistigma preventive programs into mainstream schools.
Keywords: inclusive education; children with special needs; stigma; parent’s perception; Type of access: Gated Access